Isolation, genomic characterization, and mushroom growth-promoting effect of the first fungus-derived Rhizobium - Hua, Zhongyi; Liu, Tianrui; Han, Pengjie; Zhou, Junhui; Zhao, Yuyang; Huang, Luqi; Yuan, Yuan (Frontiers in Microbiology, 2022)
Polyporus umbellatus is a well-known edible and medicinal mushroom and some bacteria isolated from mushroom sclerotia may have beneficial effect on its host. These mushroom growth promoting bacteria (MGPB) is of great significance in the mushroom production. In this work, we aimed to isolate and identify MGPB from P. umbellatus sclerotia. Using agar plate dilution method, strain CACMS001 was isolated from P. umbellatus sclerotia. The complete genome of CACMS001 was sequenced using PacBio platform and the phylogenomic analysis indicated that CACMS001 could not be assigned to known Rhizobium species. In co-culture experiments, CACMS001 increased mycelial growth of P. umbellatus and Armillaria gallica, and increased xylanase activity in A. gallica. Comparative genomic analysis showed that CACMS001 lost almost all nitrogen fixation genes but specially acquired one redox-cofactor cluster with pqqE, pqqD, pqqC and pqqB involved in the synthesis of pyrroloquinoline quinone (PQQ), a peptide-derived redox participating in phosphate solubilization activity. Strain CACMS001 has the capacity to solubilize phosphate using Pikovskaya medium, and the phnA and phoU involved in this process in CACMS001 were revealed by qRT-PCR. CACMS001 is a potential new Rhizobium species and is the first identified MGPB belonging to the Rhizobium. The application of this novel bacterium would take vital part in P. umbellatus, A. gallica and other mushroom cultivation.